Fermented rice bran extract delays skin aging by increasing the synthesis of collagen and elastin - Yan, Xin; Yang, Meiqing; Cai, Xuyi; Shen, Yiwei; Jiang, Ruihan; Huang, Rizhong; Shi, Huai-Kai; Cheng, Gregory; Wang, Yiwei; Tan, Qian; Cheng, Yuen Yee; Xue, Nannan (Frontiers in Pharmacology, 2025)
BackgroundRice bran is the outer layer of rice grains (Oryza sativa). Due to its rich bioactive components, it has long been used in cosmetics. However, the mechanism by which it delays skin aging remains unclear.MethodsIn this study, volatile polar solvents combined with microbial fermentation were utilized to enhance the yield and bioavailability of functional components in rice bran extract (RBE). The crude RBE was fermented with Aspergillus oryzae for 14 days to promote enzymatic decomposition into smaller and more bioavailable molecules. The components in the fermented RBE were qualitatively analyzed by UPLC-QTOF-MS/MS. The expression of collagen in two-dimensional and three-dimensional cell cultures was evaluated by qPCR technology. The expressions of collagen and elastin and the changes in water content and elastic modulus in the skin of mice were evaluated by histopathology, immunofluorescence staining, and transepidermal water loss (TEWL).ResultsThrough UPLC-QTOF-MS/MS analysis, eight key compounds, including azelaic acid, ferulic acid, γ-tocotrienols, and squalene, were identified in RBE, mainly lipids and polyphenols. The treatment of RBE significantly upregulated the expression of type I collagen in MSF cells and the expression of type III collagen in MSF 3D cell spheres (by approximately 12 times). The results of tissue staining showed that the content of collagen in the skin after RBE treatment increased by 10% compared with the control group. The results of immunofluorescence staining confirmed that RBE could increase the content of elastin in the skin. The TEWL results showed that the skin moisture content and elastic coefficient of mice treated with RBE increased by more than 10% compared with those of the untreated group.ConclusionBoth in vitro and in vivo studies have shown that RBE can significantly improve the synthesis of collagen and elastin in the skin, reduce water loss in mouse skin, increase collagen deposition in the skin, and ultimately improve skin elasticity and overall quality. This green, solvent-efficient, and fermentation-enhanced approach offers a sustainable strategy for utilizing rice bran as a high-value cosmetic ingredient with strong potential for skincare applications.